Plant-Derived Medicines for Sciatica: A Comprehensive Review - Narges Lavari; Niusha Esmaealzadeh; Roja Rahimi; Alireza Abbasian (Tehran University of Medical Sciences, 2024)
Sciatica commonly refers to radicular leg pain which is mainly caused by lumbar disc herniation (LDH) and affects the daily functional ability of many patients in the world. However, according to the side effects and short-term benefits of its treatments, new therapeutic agents such as natural products are needed. The aim of this study was to comprehensively review the effectiveness of plant-derived products for the treatment of sciatica. Electronic databases, including Medline (via PubMed), Scopus, and Web of Science, were searched from inception to 17 August 2023 for this comprehensive review. English language papers reporting preclinical and clinical evaluations of the effectiveness of herbal products, including medicinal plants, multi-component herbal preparations, and phytochemicals on sciatica, radicular pain, or LDH, were included. Studies on neuropathic pain due to reasons other than sciatica, radicular pain, or LDH were excluded. From a total of 5666 papers identified in the primary search, 16 (including 4 clinical and 12 preclinical studies) were finally included. Most of the plant-derived treatments mentioned in this review belonged to the polyphenol family or contained high concentrations of various polyphenols. From the results obtained, polyphenols relieved sciatica by reducing inflammation and oxidative stress, mainly through the inhibition of mitogen-activated protein kinases pathways. In conclusion, plant-derived medicines have the potential to improve the quality of life and functional ability of sciatica patients by relieving symptoms. However, further preclinical and clinical studies are suggested to prove the safety and efficacy of such herbal medicines for sciatica.